Mutagenicity and cytotoxicity evaluation of photo-catalytically treated petroleum refinery wastewater using an array of bioassays. (February 2017) - Iqbal, Munawar; Nisar, Jan; Adil, Muhammad; Abbas, Mazhar; Riaz, Muhammad; Tahir, M. Asif; Younus, Muhammad; Shahid, Muhammad
Abstract: Degradation and detoxification of petroleum refinery wastewater (PRW) was carried out by advanced oxidation processes (UV/TiO2 /H2 O2 and gamma radiation/H2 O2 ). Response surface methodology (RSM) was used to optimize the independent variables. The cytotoxicity was evaluated using Allium cepa, brime shrimp and haemolytic assays; whereas mutagenicity was tested by Ames tests (TA98 and TA100 strains). Maximum reductions in COD and BOD were recorded as 78% and 87% for UV/TiO2 /H2 O2 and 77% and 86% for gamma ray/H2 O2, respectively. Treatments with both methods at optimized conditions reduced the cytotoxicity and mutagenicity of PRW, however, UV/TiO2 /H2 O2 system was found slightly efficient as compared to gamma ray/H2 O2 . From the results, it can be concluded that AOP's can successfully be utilized for the degradation of toxic pollutants in petroleum refinery wastewater. Moreover, the bioassays used in this study offered a good reliability for checking the detoxification of treated and un-treated PRW wastewater. Highlights: Advanced oxidation processes for the treatment of refinery wastewater were investigated. Independent variables were optimized through response surface methodology. The toxicity and mutagenicity profiles of raw and treated wastewater were evaluated. The investigated method was found to be very promising for the de-contamination and detoxification of toxic agents in wastewater.